Inaccurate rotational component position in image-free navigated unicompartmental knee arthroplasty - Akihiko Toda; Kazunari Ishida; Tomoyuki Matsumoto; Hiroshi Sasaki; Koji Takayama; Ryosuke Kuroda; Masahiro Kurosaka; Nao Shibanuma (Elsevier, 2016)
Background/Objective: The success of unicompartmental knee arthroplasty (UKA) is highly dependent on the accuracy of component and leg alignment. Computer-assisted surgery is gaining popularity in total knee arthroplasty with numerous studies reporting improved accuracy and decreased variability in implant position and postoperative limb alignment compared with conventional techniques. However, literature evaluating the accuracy of computer-navigated UKA is limited. Therefore, this study aimed to investigate the accuracy of component positions in navigated UKA using a three-dimensional (3D) image-matching system. To the best of our knowledge, this study is the first to evaluate the accuracy of implant-placement position in UKA using 3D image-matching systems. Methods: Twenty-three knees in 22 patients (9 men, 13 women) underwent computer-assisted UKA performed by a senior surgeon from 2011 to 2013. All surgeries were performed with measured resection techniques using an image-free-navigation system. We recorded the coronal, sagittal, and rotational bone-resection angles towards the mechanical axis in the distal femur and proximal tibia using image-free navigation intraoperatively. The coronal, sagittal, and rotational alignments of the femoral and tibial components were also measured using the 3D image-matching system, and the accuracy of the navigated UKA was evaluated. The rotational alignment of the femur and tibia was defined as surgical epicondylar axis and Akagi's line, and a deviation over 3° from the AA was defined as an outlier. Results: We observed coronal outliers for the femoral component in four of the 23 patients, and for the tibial component in three of the 23 patients. We also observed sagittal outliers for the femoral component in five of 23 patients, and for the tibial component in three of the 23 patients. Twenty-two tibial components were placed in external rotation relative to the rotational reference line. Conclusion: In both coronal and sagittal alignments, there were a definite proportion of outliers. The ratio of outliers in rotational alignment was especially higher than that in coronal and sagittal alignments. In UKA, the identification of bony landmarks is difficult because of the small operation field. Therefore, careful surface mapping of particular bony landmarks is necessary, and it is not enough to use image-free navigation system in UKA.